2021
DOI: 10.3390/su13116250
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Response of Vegetation to Rainfall and Air Temperature Fluctuations in the Sahel: Case Study in the Forest Reserve of Fina, Mali

Abstract: Forests constitute a key component of the Earth system but the sustainability of the forest reserves in the semi-arid zone is a real concern since its vegetation is very sensitive to the climate fluctuation. The understanding of the mechanisms for the vegetation–climate interaction is poorly studied in the context of African Sahel. In this study, the characteristics of the vegetation response to the fluctuations of precipitation and temperature is determined for the forest reserve of Fina. Rainfall estimates, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
2
3
0
Order By: Relevance
“…While our study focused on Mali, it has contributed to the understanding of wider land change drivers relevant to the Sahel region as a whole. Similar to the results of our current study, other authors also reported that climate change in general and increasing drought periods in particular negatively affect the livelihoods of rural communities in Sahelian West Africa [43][44][45] and that this pushes them towards expansion of cropland and alternative livelihoods (firewood, charcoal and timber), ultimately driving land cover change (e.g., loss of wooded savannah). Thereby, land management strategies need to consider climate friendly energy and timber sources for livelihood improvement in the Sahel [46].…”
Section: Discussionsupporting
confidence: 90%
“…While our study focused on Mali, it has contributed to the understanding of wider land change drivers relevant to the Sahel region as a whole. Similar to the results of our current study, other authors also reported that climate change in general and increasing drought periods in particular negatively affect the livelihoods of rural communities in Sahelian West Africa [43][44][45] and that this pushes them towards expansion of cropland and alternative livelihoods (firewood, charcoal and timber), ultimately driving land cover change (e.g., loss of wooded savannah). Thereby, land management strategies need to consider climate friendly energy and timber sources for livelihood improvement in the Sahel [46].…”
Section: Discussionsupporting
confidence: 90%
“…Similar to the results of our current study, other authors also reported that climate change in general and particularly through increased drought periods negatively affects the livelihoods of local communities' in Sahelian West Africa ( [34]; [35]; [36] and that this pushes them towards expansion of cropland and search for alternative livelihoods (firewood, charcoal and timber), ultimately driving land cover change (ex. loss of wooded savannah) as observed in our study.…”
Section: Correlation Analysissupporting
confidence: 89%
“…The technology requires skills in implementation, maintenance, and use. However, 46% of the studied districts' rural communities do not have formal education (Sanogo et al, 2021). In situations when there are no industries or equivalent employers to provide local people with income-generating opportunities, the implementation of small-scale SBISs with the provision of required skills could be a useful option to enhance the livelihood of rural communities.…”
Section: Discussion Prospects For Sbiss Development In Malimentioning
confidence: 99%
“…Areas receiving annual rainfall >800 mm were found to be suitable as well. However, the spatial and temporal variability of rainfall as evidenced in southern Mali (Ebi et al, 2011;Akinseye et al, 2020;Sanogo et al, 2021) could be a limiting factor to recharge groundwater aquifers. This could also impact the sustainability of SBISs.…”
Section: Discussion Prospects For Sbiss Development In Malimentioning
confidence: 99%
See 1 more Smart Citation